Tipologi Pemikiran Cendikiawan Muslim - Ridwan, Ridwan; Rosyidi, Abdul Wahab (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
In the process of the development of intellectualsm, the role of Moslem scholars who were successful to make a dynamic atmosphere in Islamic thoughts to point out. They’re popular and well-socialized thoughts develop and bring posit if on the knowledge and the perception of religion in the society. The development of the scholar's Islamic thought has different characteristic and pattern which is interesting to analyze. The purpose of analysis is to enlarge our knowledge on the Islamic thought, especially those which were written in daily newspaper